Melissa officinalis L. ethanolic extract inhibits the growth of a lung cancer cell line by interfering with the cell cycle and inducing apoptosis. Issue 6 (23rd May 2018) - Magalhães, D. B.; Castro, I.; Lopes-Rodrigues, V.; Pereira, J. M.; Barros, L.; Ferreira, I. C. F. R.; Xavier, C. P. R.; Vasconcelos, M. H.
Abstract : Melissa officinalis is a plant from the family Lamiaceae, native in Europe particularly in the Mediterranean region. Abstract : Melissa officinalis is a plant from the family Lamiaceae, native in Europe particularly in the Mediterranean region. Given our interest in identifying extracts and compounds capable of inhibiting tumor cell growth, and given the antioxidant content and the high consumption of Melissa officinalis in Portugal, this study aimed to test the tumor cell growth inhibitory activity of five different extracts of this plant (aqueous, methanolic, ethanolic, hydromethanolic and hydroethanolic) in three human tumor cell lines: MCF-7, AGS and NCI-H460. All extracts decreased cell growth in all cell lines in a concentration-dependent manner. The ethanolic extract was the most potent one, presenting a GI50 concentration of approximately 100.9 μg mL −1 in the NCI-H460 lung cancer cells. This extract was characterized by LC-DAD-ESI/MS regarding its phenolic composition, revealing rosmarinic acid as the most abundant compound. The GI75 concentration of this extract affected the cell cycle profile of these cells. In addition, both the GI50 and the GI75 concentrations of the extract induced cellular apoptosis. Moreover, treatment of NCI-H460 cells with this extract caused a decrease in pro-caspase 3 and an increase in p53 levels. This study emphasizes the relevance of the study of natural products as inhibitors of tumor cell growth.